Spiritual and Moral Development through Sufi Orders: The Role of Tarekat Qadiriyah Wa Naqsabandiyah in Shaping Santri’s Character - Jumhur; Duski Ibrahim; Munir (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aimed to analyze the internalization process of the teachings of the Tarekat Qadiriyah Wa Naqsabandiyah within both formal and informal educational systems at Pondok Pesantren (Islamic Boarding School) Aulia Cendekia. This research focused on exploring the extent to which these teachings were integrated into the pesantren curriculum and their impact on the character development of the students (santri). Utilizing a qualitative descriptive method through observations, interview and literature review, the study emphasized the integration of Tarekat values in the teaching of classical Islamic texts, daily dzkir (remembrance of God), and weekly wirid (devotional practices). Findings showed that the Tarekat teachings had been comprehensively integrated into both the academic and non-academic aspects of pesantren educational system. The kyai (spiritual leader) played a pivotal role as a spiritual guide, assisting santri in understanding and practicing Sufi teachings. This internalization process had significantly contributed to the development of discipline, spiritual awareness and emotional balance among the students. It can be concluded from this study that the application of Tarekat Qadiriyah Wa Naqsabandiyah has successfully fostered students who are intellectually competent and spiritually resilient. However, continuous adaptation of teaching methods is necessary to maintain relevance in the face of modern challenges. The internalization of these teachings played a crucial role in balancing spirituality with formal education in pesantren environment.